LINGUISTIC FEATURES OF «DANCE» TERMINOLOGY IN UZBEK AND ENGLISH - Khudoyberdieva, Oyjamol (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article explores the concept of dance terminology and its linguistic characteristics in both Uzbek and English. It is discussed the importance of a rich vocabulary for creating dance terminology in Uzbek. This article delves into the fascinating world of dance terminology, exploring its linguistic features in both Uzbek and English.